Experimental and numerical research on the mode I delamination of looped fabric reinforced laminate. (1st February 2020) - Yu, Jian; Zhou, Chuwei; Li, Shuguang
Abstract: The fabric structure of looped fabric reinforced laminate (LFRL) was investigated based upon braiding process and microscopy imaging. Fiber bridging in double cantilever beam (DCB) specimens manufactured of plain weave fabric laminate (PW) and LFRL was studied experimentally. An FE model for LFRL DCB specimen considering large-scale bridging was developed based on the experimental research and the numerical theory. The studied loop-bridging tractions were used with the cohesive model to describe crack growth, and a good agreement between numerical and experimental result was demonstrated. The proposed FE model was also applied to investigate the mode I fracture properties of various LFRL DCB specimens with different initial crack length, length of loops and density of loops, which could be referred by the composites design.